Autonomy and Decision-Making Capacity in Older Adults with Mild Cognitive Impairment - Giber, Fabiana (Revista del Hospital Italiano de Buenos Aires, 2026)
Can a person with mild cognitive impairment make decisions about their own medical care? The editors of the Revista del Hospital Italiano de Buenos Aires invited two distinguished experts to reflect on a hypothetical clinical scenario.Dr. Fabiana Giber discusses the limits of autonomy, the role of the family, and the importance of assessing decision-making capacity on an individual basis before making decisions on behalf of the patient.Read Dr. O. M. Mazza’s commentary: [link]
Keywords: Mild Cognitive Impairment; Decision Making; Personal Autonomy; Comprehensive Geriatric Assessment